Low_latitude ionospheric height variation as observed by meridional ionosonde chain: Formation of ionospheric ceiling over the magnetic equator - Takashi Maruyama; Jyunpei Uemoto; Mamoru Ishii; Takuya Tsugawa; Pornchai Supnithi; Taradol Komolmis (My University, 2014)
Abstract A multipoint ionosonde observation campaign was conducted along the magnetic meridional plane in Southeast Asia to study ionosphere‐thermosphere coupling. One station was near the magnetic equator and two of the other stations were at off‐equatorial latitudes (∼10° magnetic latitude). The daytime ionospheric peak height ( h m F 2 ) was analyzed for each season during the solar minimum years, 2006–2007 and 2009. The peak height increased for ∼3 h after sunrise at the magnetic equator and off‐equatorial latitudes, as expected from the daytime upward E × B drift. The apparent upward drift at the magnetic equator ceased before noon, while the drift at the off‐equatorial latitudes continued upward and the layer height exceeded the equatorial height around noon. The noontime limited layer peak height at the magnetic equator, which was termed the ionospheric ceiling, did not depend on the season, while the maximum peak height at the off‐equatorial latitudes largely varied with each season. Numerical modeling using the SAMI2 code was conducted and the features of the ionospheric ceiling were reproduced quite well. The dynamical parameters provided by the SAMI2 modeling runs showed that the ionospheric ceiling is formed by the field‐aligned plasma diffusion, which is a part of the fountain effect.
Keywords: Noon; Ionosonde; Magnetic dip; Ionosphere and magnetosphere dynamics